2010
DOI: 10.1111/j.1440-1681.2010.05421.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin AT1 receptor activation mediates high glucose‐induced epithelial–mesenchymal transition in renal proximal tubular cells

Abstract: SUMMARY1. Renal tubular epithelial cells can undergo epithelial to mesenchymal transition (EMT) under hyperglycaemic conditions, which is associated with renal interstitial fibrosis. Activation of the renin-angiotensin system (RAS) is involved in diabetic nephropathy. The present study investigated the positive role of angiotensin AT 1 receptors in high glucose-induced EMT in cultured tubular epithelial cells.2. A rat kidney proximal tubular epithelial cell line (NRK-52E) was used in the present study. Levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
36
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 42 publications
8
36
0
1
Order By: Relevance
“…The RAS system increases expression of MMPs and modulates the balance between MMPs and tissue inhibitors of MMPs (TIMPs) in many heart and renal diseases (21)(22)(23)(24). Previous cancer studies have demonstrated that AngII augments the migration and invasion of choriocarcinoma cells through the AT1R and induces MMP-2 and MMP-9 expression in gastric cancer cells (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…The RAS system increases expression of MMPs and modulates the balance between MMPs and tissue inhibitors of MMPs (TIMPs) in many heart and renal diseases (21)(22)(23)(24). Previous cancer studies have demonstrated that AngII augments the migration and invasion of choriocarcinoma cells through the AT1R and induces MMP-2 and MMP-9 expression in gastric cancer cells (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…14) TGF-β 1 and CTGF have been found to be up-regulated in both experimental and human DN, and to be associated with EMT, 7,10,11,[15][16][17][18][19][20][21] supporting a key role for these signaling molecules. A previous study in diabetic rats showed that using fasudil as a treatment also decreased EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data suggest that high glucose was able to induce EMT in HK-2 cells, consistent with previous studies. 17,38) The molecular mechanisms underlying EMT remain incompletely understood. Multiple intracellular signaling pathways are thought to be involved in EMT regulation, including TGF-β 1 /Smad, Wnt and p38 MAPK.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the data presented in this paper, we propose a role for the AT 2 receptor in the synthesis of fibronectin, in that the increased fibronectin response to ANG II was completely inhibited by the AT 2 receptor antagonist PD123319, while the AT 1 receptor antagonist losartan had no effect. Despite the fact that several studies have suggested that ANG II-induced fibronectin synthesis is mediated by AT 1 rather than AT 2 signaling, the interpretation relied on use of pharmacological concentrations of losartan that can compete at high concentrations for AT 2 receptor sites (38,41,51). Moreover, this is the first study to investigate the role of ANG AT 1 and AT 2 receptors in ANG II-induced fibronectin synthesis in cultured proximal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%